The Atilogwu dance - Mackay, Mercedes; Ene, Augustine (International Library of African Music, 1957)
This dance is now being seen quite frequently in London and some other European cities, and is especially welcome to those interested in African culture. For years the more serious minded of us were not permitted to see the virile West African dances in their original form because it was feared by their African exponents that they would give the impression of being “primitive” in the derogatory sense of that word. But a better form of nationalism is now evident, with splendid musicians like Ghanaian Philip Gbeho, and Nigerian E. L. Lasibikan proudly showing African culture to the world in its untampered form. Africans are becoming less ashamed of a naked torso than a Scot is ashamed of his naked knees and thighs when he dons his traditional kilt.
Keywords: African Music